Population Pharmacokinetic/ Pharmacodynamic Modelling of Auditory‐Evoked Event‐Related Potentials with Lorazepam. Issue 2 (27th September 2017) - Lombard, Aurélie; Brittain, Claire; Wishart, Graham; Lowe, Stephen; McCarthy, Andrew; Landschulz, William; Dorffner, Georg; Anderer, Peter; Yuen, Eunice
Abstract: Event‐related potentials (ERPs) are commonly used in Neuroscience research, particularly the P3 waveform because it is associated with cognitive brain functions and is easily elicited by auditory or sensory inputs. ERPs are affected by drugs such as lorazepam, which increase the latency and decrease the amplitude of the P3 wave. In this study, auditory‐evoked ERPs were generated in 13 older healthy volunteers using an oddball tone paradigm, after administration of single 0.5 and 2 mg doses of lorazepam. Population pharmacokinetics (PK)/pharmacodynamics (PD) models were developed using nonlinear mixed‐effects methods in order to assess the effect of lorazepam on the latency and amplitude of the P3 waveforms. The PK/PD models showed that doses of 0.3 mg of lorazepam achieved approximately half of the maximum effect on the latency of the P3 waveform. For P3 amplitude, half the maximum effect was achieved with a dose of 1.2 mg of lorazepam. The PK/PD models also predicted an efficacious dose range of lorazepam, which was close to the recommended therapeutic range. The use of longitudinal P3 latency data allowed better predictions of the lorazepam efficacious dose range than P3 amplitude or aggregate exposure–response data, suggesting that latency could be a more sensitive parameter for drugs with similar mechanisms of action as lorazepam and that time course rather than single time‐point ERP data should be collected. Overall, the results suggest that P3 ERP waveforms could be used as potential non‐specific biomarkers for functional target engagement for drugs with brain activity, and PK/PD models can aid trial design and choice of doses for development of new drugs with ERP activity.